TOXIC PARENTING AND ITS IMPACT ON CHILDREN'S LANGUAGE ETHICS - Riza Khairani Harahap; Daulay, Annisa Arrumaisyah (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2023)
This study focuses on examining parental practices in raising children. Parenting patterns encapsulate the methods employed by parents to nurture, guide, and lead their children within the family context. A recently emerged concept known as